2015
DOI: 10.1055/s-0034-1391990
|View full text |Cite
|
Sign up to set email alerts
|

ERCP-guided cholangioscopy using a single-use system: nationwide register-based study of its use in clinical practice

Abstract: The single-operator peroral cholangioscopy technique is an advanced technique for intraluminal visual inspection, and for therapeutic intervention of the biliary and pancreatic ducts. However, there is a significantly increased risk of intra- and postprocedural adverse events. Thus, this method should preferably be performed at tertiary referral centers in carefully selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…With regard to the adverse events of single‐operator cholangioscopy‐guided biopsy, a single centre prospective study with literature review of 646 patients reported an overall procedure‐related adverse events of 9.4%‐21.4% . Another large cohort study showed that the SpyGlass procedure (408 patients) was associated with a higher rate of intraprocedure adverse events (OR 3.01, 95%CI 1.52‐5.36) than conventional ERCP procedures (35 944 patients), and the rate of post‐procedure adverse events was higher in the early study period than in the late study period (25.3% vs 15.6%, P = 0.017), which highlights the importance of personnel training in reducing single‐operator cholangioscopy‐related adverse events . The rate of adverse events of diagnostic direct peroral cholangioscopy can be as high as 10% …”
Section: Resultsmentioning
confidence: 99%
“…With regard to the adverse events of single‐operator cholangioscopy‐guided biopsy, a single centre prospective study with literature review of 646 patients reported an overall procedure‐related adverse events of 9.4%‐21.4% . Another large cohort study showed that the SpyGlass procedure (408 patients) was associated with a higher rate of intraprocedure adverse events (OR 3.01, 95%CI 1.52‐5.36) than conventional ERCP procedures (35 944 patients), and the rate of post‐procedure adverse events was higher in the early study period than in the late study period (25.3% vs 15.6%, P = 0.017), which highlights the importance of personnel training in reducing single‐operator cholangioscopy‐related adverse events . The rate of adverse events of diagnostic direct peroral cholangioscopy can be as high as 10% …”
Section: Resultsmentioning
confidence: 99%
“…Although the incidence rate of adverse events appears low (6.1%) in our analysis, some studies reported high complication rates of treatment with SOPOC. Lubbe et al . reported that SOPOC was associated with post‐procedural adverse events in 19.1% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence rate of adverse events appears low (6.1%) in our analysis, some studies reported high complication rates of treatment with SOPOC. Lubbe et al 40 reported that SOPOC was associated with post-procedural adverse events in 19.1% of patients. Tieu et al 21 and Sethi et al 41 reported that the adverse event rate of ERCP combined with SOPOC was twofold higher than that of ERCP alone.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is a component of selection bias when patients are chosen to undergo POC. A recent study 60 , completed in Sweden based on a national registry, reported that the risk for intra- and post-procedural adverse events is significantly increased when a patient undergoes POC in conjunction with ERCP, as opposed to ERCP alone. However, the study also noted that in a multivariate analysis that adjusted for confounders, the risk for pancreatitis and cholangitis was not increased.…”
Section: Discussionmentioning
confidence: 99%